KINERJA KARYAWAN DIPENGARUHI OLEH PELATIHAN MELALUI DISIPLIN KERJA DI PT. TRIMULIA BANGUN PERSADA BEKASI - Nabilla Ayu Fauziah; Edy Sanusi Silitonga (Jurnal Ekonomi dan Industri, 2023)
This study aims to determine the effect between Training on Employee Performance through Work Discipline at PT. Trimulia Bangun Persada. The research method used is quantitative method with a sampling technique using non-probability sampling technique that is saturated sample. analysis method using path analysis. The research results show that: 1) Training has positive effect but no significant on employee performance at PT. Trimulia Bangun Persada. 2) Training has a positive and significant effect on employee work discipline at PT. Trimulia Bangun Persada. 3) Work discipline has a positive and significant effect on employee performance at PT. Trimulia Bangun Persada. 4) Training affects employee performance through work discipline at PT. Trimulia Bangun Persada.